People equity model as an effort to increase employees' intention to stay - Tatin Wahyanto; Stefanus Supriyanto; Nyoman Anita Damayanti; Sri Hartini; Retno Lestari (SAGE Publishing, 2020)
Background: The high turnover rate in the healthcare industry needs serious attention since it influences hospital service quality. So, there is a need to develop a new framework known as people equity, that can be used to manage intangible assets and reduce employees' intention to leave. The purpose of this study therefore was to develop a model of people equity as a strategy for enhancing employees' intention to stay. Design and methods: An analytical cross-sectional design was used to measure the associations between variables. 154 respondents were selected from stratified random sampling technique. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyze the measurement model. Results: The results indicated that people equity was influenced by organizational factors (P=0.210), individual factors (P=0.183), and occupational factors (P=0.141). In addition to this, predictors for employees' intention to stay were people equity (P=0.432), individual factors (P=0.308), and environmental factors (P=0.117). Conversely, working and marital status, environment, and workload have no significant effect on people equity and intention to stay. Conclusions: People equity was influenced by organizational, individual, and occupational factors through the implementation of the Human Resources System. People equity model increased employees' intention to stay by improving organizational factors.